Uso del Partograma como instrumento de Vigilancia clínica del trabajo de parto en el Hospital Minsa II-2– Tarapoto. Enero - mayo 2015 - Nuñez Dávila., Juana María (2016)
This study aimed to determine if the partograph has been used for clinical monitoring of labor through the complete record of information for health professional obstetrics MOH II Hospital - 2 Tarapoto, January-May 2015, quantitative, simple descriptive cross-sectionalstudy with prospective data collection whose sample was 153 women with clinically driven labor using the partograph. The results were: 76.2% (117) of deliveries, the obstetrics service professionals using partograph for labor management. 73.6% (112) of normal births were attended by midwives or obstetric internal. Regarding the percentage of cases in which the professionals handle the partograph for making adequate delivery care behaviors: in 79.2% (121) meets the registration of the actual curve and the curve warning; in 66.9% (102) properly record the progress of cervical dilation; in 80.0% (122) correctly records the uterine contractions; and 80.8% (123) correctly recorded fetal heart rate. The average duration of periods of labor was 396 minutes (6.36 hours) for the first stage of labor; 16 minutes expulsive period; and 11.40 minutes on average for the period of delivery. 79.2% (121) patients completed the labor condition in normal vaginal delivery; while 20.8% (32) ended in cesarean section. In conclusion: In 76.2% (117) of deliveries, service professionals used the partograph obstetrics and record complete information for clinical monitoring of labor in the service of obstetrics MOH II Hospital - 2 Tarapoto.